2013
DOI: 10.1159/000351106
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Education for Oral Contraceptive Use in Korea: Results from the Fourth Korean National Health and Nutrition Examination Survey 2007-2009

Abstract: Background/Aims: To compare the prevalence of contraindications to oral contraceptive (OC) use between OC users and nonusers and to identify high-risk groups related to contraindications to OC use among OC users. Methods: This health-interview survey is part of the Fourth Korean National Health and Nutrition Examination Survey 2007-2009. Of 13,561 women who participated in the survey, 672 were OC users and 3,720 were OC nonusers. The adjusted proportions of contraindications to OC use were measured according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, many Koreans are reluctant to take hormonal pills for a long duration, and they tend to show deteriorating compliance to treatment because of cultural bias against OCs. 11,12 Therefore, there is a need for another long-term hormonal treatment that can be maintained with better patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…However, many Koreans are reluctant to take hormonal pills for a long duration, and they tend to show deteriorating compliance to treatment because of cultural bias against OCs. 11,12 Therefore, there is a need for another long-term hormonal treatment that can be maintained with better patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that although preabortion counseling can improve COC use in the immediate postabortion period, it does not improve the continued use rate. A study in Korea showed that education programs for COC use are necessary to improve knowledge about the correct use of COCs and their contraindications [25] . A systematic review by Halpern et al [26] indicated that a combination of intensive counseling and multiple contacts and reminders during follow-up may be needed to improve adherence and acceptability of COC use.…”
Section: Discussionmentioning
confidence: 99%
“…Because girls who get pregnant commonly undergo an induced abortion or leave school, contraception in adolescents should be addressed with high priority. Nevertheless, there have been very few studies evaluating the status of contraceptive use during adolescence in Korea [56], which is an important process in order to develop interventions for enhancing contraceptive use among adolescents.…”
Section: Introductionmentioning
confidence: 99%